Professional safety and health strategies for the years 2004–2006 - Šukys, Ritoldas; Čyras, Petras (Technological and Economic Development of Economy, 2004)
The purpose of this work is to set down strategic directions of safety and health for the years 2004–2006. To achieve the objective European Communities Professional safety and health strategies for 2002–2006 were estimated, employee’s present state of health and safety analysis was done, professional health and safety scientific researches results were used. In this work the methods of selection, poll, statistic‐analysis, mathematical modulation were used. The main result of the research is professional health and safety strategic directions for the years 2004–2006: • creating of good physical conditions at work places (increasing work welfare); • consolidating and improving of preventive culture; • modelling and implementing of professional health and safety at work policy that is a component of social policy. Such directions are determined by: • the increased amount of accidents and industrial diseases in separate sorts of economical activities and performing specific work exceeds Lithuania’s average; • incompletely understood the EU and prosecuted preventive principles, written in professional health and safety certificates; • the lack of realizing complex preventive means, considering such important work quality elements as necessary skills and qualification, attribution of work relationship and work organization, work time; • faulty work quality that shows not only in the amount of accidents and professional diseases, but also in country’s and company’s economic and social outcome, poor business image, which depends on safe and healthy working conditions. Article in Lithuanian. Profesinės saugos ir sveikatos strateginės kryptys 2004–2006 metams First Published Online: 21 Oct 2010